The reality of privatization in Algeria - Sociological study - TAIBI, Hocine; TOUNSI, Faiza (Social Sciences Journal)
The topic of Privatisation or the transfer of public property to the private sector or what it’s termed as privatisation is recently considered as a centre of noticeable international concern. Most countries nowadays, with their different economic and political orientations went to abandon a lot of public economic institutions and giving it to the private sector. Before moving to the analysis of the legal and organizational frame for the start of the privatisation of public institutions process in Algeria, we take a look at the essence of privatisation and its real motives and reality in Algeria, then the fields of applying it in Algeria.